2018
DOI: 10.1039/c8ta03446j
|View full text |Cite
|
Sign up to set email alerts
|

Thin film nanocomposite nanofiltration membranes from amine functionalized-boron nitride/polypiperazine amide with enhanced flux and fouling resistance

Abstract: Thin film composite (TFC) nanofiltration (NF) membranes typically used for drinking water treatment applications are susceptible to fouling by natural organic matter (NOM) which adversely affects the permeation and separation efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(80 citation statements)
references
References 67 publications
3
76
1
Order By: Relevance
“…Final experiments confirmed the strong adhesion of nanosheets to the membrane surface, and showed that no nanosheets were detached [ 203 ]. By contrast in the previous study of Abdikheibari et al [ 210 ], aminated BN nanosheets were embedded in a PPA thin layer, and achieved flux improvement and enhanced fouling resistance of 13.4% and 5.2%, respectively. These results highlight the importance of surface exposure of nanosheets for stacked TFC membranes [ 203 ].…”
Section: Nanosheet Induced Fouling Mitigationcontrasting
confidence: 72%
“…Final experiments confirmed the strong adhesion of nanosheets to the membrane surface, and showed that no nanosheets were detached [ 203 ]. By contrast in the previous study of Abdikheibari et al [ 210 ], aminated BN nanosheets were embedded in a PPA thin layer, and achieved flux improvement and enhanced fouling resistance of 13.4% and 5.2%, respectively. These results highlight the importance of surface exposure of nanosheets for stacked TFC membranes [ 203 ].…”
Section: Nanosheet Induced Fouling Mitigationcontrasting
confidence: 72%
“…Membrane-based separation offers a scalable, economically and environmentally friendly tool for numerous applications, e.g., biochemical and pharmaceutical processing, water purication, and wastewater treatment. [1][2][3][4][5] Although the interest in developing high-performance membranes has been growing from diverse inorganic, organic, and composite materials, [6][7][8][9][10][11][12][13] a longstanding goal in membrane technology is still to pursue an ideal membrane with a high permeance, good selectivity and strong fouling resistance.…”
Section: Introductionmentioning
confidence: 99%
“…1TPa, yield strength 35 GPa), atomic flatness, sufficient rigidity,u ltra-low density (2.1 gcm À3 ), and low cost. [10] However,a lthough some attempts have been made towards BN/polymer hybrid membranes, [11] progress is generally very limited, and there are only afew reports of BN membranes for water and organic solvent separations. [9] Hence,BNisconsidered to be anovel and leading candidate for developing separation membranes with superior comprehensive performance.…”
Section: Introductionmentioning
confidence: 99%